(untitled) (London, 1997)
Recent advances in protein structural biology, coupled with new developments in human genetics, have opened the door to understanding the molecular basis of many metabolic, physiological, and developmental processes in human biology.
Keywords: Molecular biology,Cells,Sinh học tế bào